José Hernández: El gaucho Martín Fierro; La vuelta de Martín Fierro. Edición de Luis Sáinz de Medrano. 3 e. Madrid, Cátedra, c. 1982, 351 p. (Letras Hispánicas), 18 x 11 cm. - Curia, Beatriz (1983)
Fil: Curia, Beatriz. Universidad de Buenos Aires